MENGGAGAS INTEGRASI MULTIKULTUR PEMBELAJARAN MATEMATIKA: suatu telaah etnomatematika - Sirate, Sitti Fatimah S. (AULADUNA: Jurnal Pendidikan Dasar Islam, 2015)
Abstract: This paper aims to: (1) assess the multicultural education and ethno-mathematics, (2) initiating the integration of ethno-mathematics in learning, and (3) revealing a model of curriculum that integrates the ethno-mathematics in mathematic learning. The essence of multi-cultural education is to have the same opportunities in a diverse life. Ethno-mathematics as a mathematical science practiced by groups of different cultures that are identified as indigenous communities, groups of workers, the professional classes, and groups of children of a certain age group. Ethno-mathematics ideas in mathematics and curriculum gives new nuances in the study of mathematics by the consideration that Indonesia consists of various races and cultures, and each tribe has its own way in solving the problems faced. Ethno-mathematic curriculum model is designed in an appropriate context and meaningful, in the form of specific cultural content oriented in the development of mathematical thinking, and it was an integration of mathematical concepts and practices into the culture of students. Abstrak: Tulisan ini bertujuan untuk: (1) mengkaji pendidikan multikultur dan ethno-matematika, (2) menggagas integrasi etnomatematika dalam pembelaja-ran, dan (3) mengungkap model kurikulum yang mengintegrasikan etno-matematika dalam pembelajaran matematika. Hakikat pendidikan multi-kultural adalah memiliki kesempatan yang sama dalam kehidupan yang beragam. Etnomatematika sebagai ilmu matematika yang dipraktikkan oleh kelompok-kelompok budaya yang berbeda yang diidentifikasi sebagai masyarakat pribumi, kelompok pekerja, kelas-kelas profesional, dan kelompok anak-anak dari kelompok usia tertentu. Gagasan etnomatema-tika dalam pembelajaran matematika dan kurikulum memberi nuansa baru dalam pembelajaran matematika dengan pertimbangan bahwa bangsa Indonesia terdiri atas berbagai suku dan budaya, dan setiap suku memiliki cara tersendiri dalam menyelesaikan masalah yang dihadapi. Model kurikulum etnomatematika dirancang dalam konteks yang sesuai dan berarti, dalam bentuk conten budaya khusus, berorientasi pengembangan pemikiran matematika, dan merupakan integrasi konsep dan praktik matematika ke dalam budaya siswa.